Shaping democracy in Indonesia: The influence of multicultural attitudes and social media activity on participation in public discourse and attitudes toward democracy - Sukidin; Choirul Hudha; Basrowi (Social Sciences and Humanities Open)
This study explores the influence of multicultural attitudes, social media activity, and participation in public discourse on democratic engagement among high school students in Indonesia. A total of 482 respondents, selected using stratified random sampling, participated through online and offline questionnaires. The results show that multicultural attitudes positively influence Attitudes toward Democracy, supporting the idea that inclusive attitudes enhance democratic participation. However, these attitudes have little effect on Participation in Public Discourse. Social media activity does not directly impact Attitudes toward Democracy but positively affects Participation in Public Discourse. Participation in Public Discourse serves as a mediator between multicultural attitudes, social media activity, and Attitudes toward Democracy. Social openness strengthens the relationships between multicultural attitudes, social media, and democratic engagement. The study's limitations include a narrow focus on high school students, cross-sectional data, and reliance on self-reported measures, which may limit the generalizability of the findings. Future studies should expand the sample, use longitudinal designs, and incorporate mixed methods to gain a deeper understanding of these relationships.